You ruined it - Higginbotham, Anastasia (Dottir Press, 2022)
"In You Ruined It, author Anastasia Higginbotham sheds light on the confusion and pain that many children feel in the aftermath of incest and sexual assault. When 11-year-old Dawn discloses that a favorite cousin sexually assaulted her, it's hard to tell what hurts more: the betrayal or the fall-out. After all, everyone always says to tell someone, but does this mean she'll never get to hang out with him again? What if he goes to jail? And the biggest question of all: How will she know if she can trust someone again? You Ruined It is a testament to an 11-year-old's experience of a confusing betrayal, her broken heart, and the loved ones who help her piece it back together."--Publisher's webpage